2016
DOI: 10.21829/myb.2007.1321229
|View full text |Cite
|
Sign up to set email alerts
|

El tamaño sí importa: los frutos grandes de Juniperus deppeana Steud. (sabino) son más susceptibles a depredación por insectos

Abstract: RESUMENEl siguiente trabajo documenta la relación entre el tamaño de los frutos (gálbulos) de Juniperus deppeana Steud. y el daño ocasionado por insectos depredadores de semillas en un fragmento de bosque de sabinos, característico del estado de Tlaxcala, México. En el estudio se seleccionaron árboles femeninos del sabino para cuantificar la maduración de los gálbulos y se clasificó la disponibilidad de éstos en tres categorías de tamaño: pequeños (5 a 9 mm), medianos (10 a 12 mm) y grandes (13 a 15 mm), cuant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 38 publications
1
5
0
7
Order By: Relevance
“…It was observed that the viability of J. deppeana seeds remained intact during their passage through the digestive tract of the majority of the mammals studied, a finding similar to that of the study conducted by Aronne and Russo (1997), who conclude that Myrtus communis seeds dispersed by the red fox maintain their viability. Moreover, these authors also found that the low viability presented by the seeds taken from the canopy was attributable to the damage caused by parasitic insects, as reported by Martínez, Sainos, Lezama-Delgado, and Angeles-Álvarez (2007), who also observed damage by parasitic insects in J. The present study found that the disperser mammals enhanced germination of J. deppeana, particularly in seeds dispersed by coyote and bobcat, compared with that of the seeds taken from the canopy.…”
Section: Qualitative Contribution Of Carnivoressupporting
confidence: 86%
“…It was observed that the viability of J. deppeana seeds remained intact during their passage through the digestive tract of the majority of the mammals studied, a finding similar to that of the study conducted by Aronne and Russo (1997), who conclude that Myrtus communis seeds dispersed by the red fox maintain their viability. Moreover, these authors also found that the low viability presented by the seeds taken from the canopy was attributable to the damage caused by parasitic insects, as reported by Martínez, Sainos, Lezama-Delgado, and Angeles-Álvarez (2007), who also observed damage by parasitic insects in J. The present study found that the disperser mammals enhanced germination of J. deppeana, particularly in seeds dispersed by coyote and bobcat, compared with that of the seeds taken from the canopy.…”
Section: Qualitative Contribution Of Carnivoressupporting
confidence: 86%
“…Las gálbulas están colocadas en pedúnculos cortos, de color verde, el mesocarpio es fibroso y fuertemente adherido a la semilla; en su madurez cambian de color a café, azul o violáceo (Zamora et al, 2010;Adams, 2008;Martínez, 1963). Estas especies producen árboles machos y árboles hembras (Martínez et al , 2007). The average height of trees of J. comitana y J. deppeana var.…”
Section: Introductionunclassified
“…Galbules are in short green peduncules, mesocarp is fibrous and strongly adhered to the seed; when mature, they change their color to Brown, blue or violet (Zamora et al, 2010;Adams, 2008;Martínez, 1963). These species produce male and female trees (Martínez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations